تراجمُ الشُّعراءِ السُّودانيين بين موسوعةِ الشِّعر السُّوداني الفصيحِ (1919-2019م) لفاطمة بوهراكة، وكتبِ التَّراجمِ السُّودانيّة. - محمد, المكاشفي إبراهيم عبدالله (Journal of Faculty of Education, 2022)
هدفت الدراسة إلى بيان الدور البيبلوغرافي الذي لعبته موسوعة الشعر السوداني الفصيح ( ١٩١٩-٢٠١٩م) ، لفاطمة بوهراكة، ومقارنته بكتب التراجم السودانية منهجاً وكماً وكيفاً،ومن هنا تتأتى أهميّة الدراسة متمثلة في فحصها لمنهج التوثيق الذي وُثِّقَ بهللشعر السوداني الفصيح إبان مائة عام فائتة. انتهجت الدراسة المنهج الوصفي ، وتوصلت إلى عدد من النتائج، أهمها: ضعف الاهتمام بالتوثيق في السودان عامة ، وخروج منهج التوثيق - في بعض كتب التوثيق السودانيِّة- عن ثلاثيّة التوثيق العلميّة، المتمثلة في السيرة الأدبيّة، والنموذج الشعري والصورة الفوتوغرافيِّة إلى الحديث عن قبيلة الشاعر وأخلاقه وأسرته. التزام موسوعة بوهراكة بالمنهج العلميّ في التوثيق وحيادها التام عن التدخل في تفاصيل الحياة الذاتيّة للشعراء الموثّق لهم، الأمر الذي ساعد على تقديم ثلاثمائة واثنين شاعراً وشاعرة بطريقة سلسة ومفهومة إلى حد كبير. اهتمام الموسوعة بشعر النساء وتقديمها لأربعين شاعرة للمكتبة العربيِّة عامة والسودانيِّة خاصة، في سبق لم تستطعه جل الكتب السودانيِّة التي توفرت على عدد خمس عشرة شاعرة فقط. This study aimed at reporting the bibliographical role that is played by the Encyclopedia of the Sudanese Eloquent Poetry (1919 – 2019) for Fatima Bohraka and comparing its methodology, quantitative and qualitative aspects with the other Sudanese bibliographies. Thus the importance of this study comes from inspecting the methodology of bibliography that is adopted during the last 100 years. The study followed the descriptive approach. The most important findings of the study are: little attention has been given to poetic bibliography all over Sudan. The deviation of bibliography – in some Sudanese bibliographies - from the trilogy of bibliography which represented in artistic bibliography, poetic sample, and the poet’s photo to discuss the poet’s tribe, personal characteristics and his family. Another finding was that Fatima Bohraka’s encyclopedia has adhered to the scientific method in bibliography and its neutral handling towards interfering in the poets private issues thus a three hundred and two he/she poets were presented in refine and understandable style to a large extent. A special attention was given to women’s poetry, so forty female poets were addressed in the Arabic library and particularly to the Sudanese library preceding most available Sudanese books that presented only fifteen female poets.